African American-religion [sic] - Raboteau, Albert J. (New York : Oxford University Press, 1952)
Examines the history of religious practice by African Americans and the development of religious institutions, regional movements, and important personalities from the time of slavery up to the twentieth century.
Includes bibliographical references (p. 137-139) and index.
Keywords: African Americans -- Religion -- Juvenile literature; African Americans -- Religion